ChemInform Abstract: Synthesis of Biaryls by Decarboxylative Hiyama Coupling. Issue 46 (November 2015) - Katayev, Dmitry; Exner, Benjamin; Goossen, Lukas J.
Abstract This is the first protocol using nontoxic but rather unreactive organosilanes as partner in the decarboxylative Hiyama coupling giving the biaryls in high yields while keeping halo functions intact.